Accuracy of telomerase in cervical lesions: a systematic review. Issue 6 (1st October 2007) - Rosa, M. I.; Medeiros, L. R.; Bozzetti, M. C.; Fachel, J.; Wendland, E.; Zanini, R. R.; Moraes, A. B.; Rosa, D. D.
Abstract : The detection of telomerase activity in cervix may provide information on cervical carcinogenesis and may be a marker to monitor cervical intraepithelial neoplasia transition. A quantitative systematic review was performed to estimate the accuracy of telomerase assay in cervical lesions. Studies that evaluated the telomerase test (telomerase repeated amplification protocol) for the diagnosis of cervix lesions and compared it to paraffin-embedded sections as the diagnostic standard were included. Ten studies were analyzed, which included 1069 women. The diagnostic odds ratio (DOR) for a positive telomerase test for low-grade squamous intraepithelial lesions (Lo-SIL) vs normal or benign lesions was 3.2 (95% CI, 1.9–5.6). The DOR for a positive telomerase test for high-grade squamous intraepithelial lesions (Hi-SIL) vs Lo-SIL, normal or benign lesions was 5.8 (95% CI, 3.1–10). For cervix cancer vs Hi-SIL, the DOR for a positive telomerase test was 8.1 (95% CI, 3.2–20.3) and for cervix cancer vs Lo-SIL, normal or benign lesions, it was 40.9 (95% CI, 18.2–91). Our data support the current hypothesis that telomerase may activate an early event in cervical carcinogenesis that could be associated with the initiation and progression of cervical lesions